Formulation and Evaluation of Nicorandil Floating Tablets Using Natural Polymers - Srivastava, Anoop Kumar; Rajput, Dharmedra Singh; gupta, Naveen; K Sharma, Neeraj (Asian Journal of Pharmaceutical Research and Development, 2023)
The present work described the pre-formulation and formulation development that led to the production of Nicorandil (NDL) floating tablets by direct compression of a homogeneous powder blend/ granules. In order to achieve the drug (NDL) release up to 24 hrs, rafting approach was selected. Studies have been carried out on rafting method by the use of natural polymers (sodium alginate, xanthan gum and guar gum) alone and their combination to get maximum rafting properties with superior drug release retarding activity. The results obtained in the rafting approach indicated that the polymer combination showed significant influence on rafting properties with maximum drug release retarding ability than individual polymers. In addition, the polymer combination of xanthan gum and guar gum resulted with maximum drug release retarding ability with poor rafting properties, whereas, the polymer combination of sodium alginate and guar gum resulted with predictable release behaviour (i.e. slightly lower retarding ability than the combination of xanthan gum and guar gum) with maximum rafting properties. As such the floating tablets prepared with rafting approach were recommended for oral controlled delivery of NDL.